PENGARUH KOMUNIKASI PEMASARAN TERHADAP PENINGKATAN JUMLAH NASABAH ASURANSI BUMI ASIH JAYA MEDAN - Yustina, Ardial Ira (Universitas Medan Area, 2012)
This research is conducted to know how execution of marketing communications by employees of Glorious Earth Asih Insurance. The issues of this research is: